Complexity reduction of multiscale UTLM cell clusters - Sewell, Phillip; Benson, Trevor M.; Vukovic, Ana; Meng, Xuesong (IEEE, 2017)
Time domain electromagnetic simulations employing unstructured tetrahedral meshes offer smooth boundary approximations and graded meshes for multiscale problems. However, multiscale effects may arise not only as a consequence of fine geometry, but also from CAD and mesh generation artifacts and it is critical that the simulation algorithms can be employed in their presence without unduly compromising their computational performance. The ability of the Unstructured Transmission Line Modeling (UTLM) algorithm to coalesce small computational cells into larger entities is a key enabler for the approach. This paper demonstrates the use of complexity reduction techniques to both notably reduce the preprocessing time required for this and as a consequence, substantially extend its capability.